TINJAUAN FASILITAS SANITASI RUMAH MAKAN DI KOTA BANDA ACEH TAHUN 2007 - Yenni Hanafiah (Jukema (Jurnal Kesehatan Masyarakat Aceh), 2011)
Yenni Hanafiah1 dan Desvita, SKM, M.Kes2Peminatan Kesehatan Lingkungan, Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Aceh, Banda Aceh, 23245Peminatan Kesehatan Lingkungan, Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Aceh, Banda Aceh, 23245Â AbstractÂ There RE 133 units of restaurants in the city of Banda Aceh, spread out in 9 (nine) sub-districts. Restaurants are one of the public places visited by many tourists either locals, national or international which requires special attention. Non-sanitized restaurants can cause health problems such as Water and Food Borne Diseases. The aim of this study is to find out the condition of sanitation facilities at restaurants in Banda Aceh in 2007. This is a descriptive study, with populations of 89 fulfilled requirements and criteria restaurants in Banda Aceh. The study used total population sampling through observational technique by using checklist in collecting data. The results indicated that 51.62% facilities of restaurants fulfill requirement; 70.31% water supplies facilities fulfilled the qualification and 29.69% did not fulfill requirements; 60,52% water waste disposal facilities fulfilled the requirement and 39.48% did not fulfill the standard; 25.81% Toilet Facilities that already meet the terms and 74.19% are not yet qualified. Bins qualify are 63.19% and 16.61% are not yet qualified. Hand washing facilities that have been 18.69% qualify and 81.31% are not yet qualified. Washing equipment and food ingredients that have been 35.6% eligible and 64.4% are not yet qualified. Equipment and prevention of entry of insects and rodents that have been 24.03% qualify and 75.97% are eligible are not yet qualified.Keywords : sanitation, food equipment, restaurant